Disability in the Qur'an: The Islamic Alternative to Defining, Viewing, and Relating to Disability - Bazna, Maysaa S. (Journal of religion, disability & health, 2005)
The purpose of this study is to seek a firsthand understanding of the Islamic position and attitude towards disability by examining the primary sources of Islamic teachingthe Qur'an and the life example of the Prophet Muhammad as preserved in his sayings and teachings (Hadith). We search the Qur'an for references to such terms as blind, mute, deaf, lame, weak, orphan, destitute/needy, and wayfarer. We attempt to understand the intent of these terms by examining the roots of the Arabic words and investigating their possible synonyms; cross-referencing the Qur'anic verses containing the same terms; and confirming the meaning with the Hadith. We conclude that the concept of disability, in the conventional sense, is not found in the Qur'an. Rather, the Qur'an concentrates on the notion of disadvantage that is created by society and imposed on those individuals who might not possess the social, economic, or physical attributes that people happen to value at a certain time and place. The Qur'an places the responsibility of rectifying this inequity on the shoulder of society by its constant exhortation to Muslims to recognize the plight of the disadvantaged and to improve their condition and status.